Introduction: Borders, Economy, Culture - Scott, James Wesley (International Journal of Contemporary Economics and Administrative Sciences, 2016)
General remarks on the relationship between borders, economy and culture as introduction to the IJCEAS special issue on <span style="font-size: 10pt; font-family: "Times New Roman", serif; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="TR">Implications of Borders on Economy and Culture. <span style="font-size: 10pt; font-family: "Times New Roman", serif; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="TR">